(untitled) (Texas Journal of Medical Science, 2025)
One of the major limitations of the traditional treatment sequence is that a substantial proportion of patients are unable to complete planned adjuvant chemotherapy. Postoperative complications, prolonged recovery, stoma-related issues, and decreased performance status frequently lead to dose reductions, treatment delays, or complete omission of systemic therapy.